Extracorporeal lung support for tracheoesophageal fistula surgical repair with free flap. Issue 7 (July 2022) - Bauer, C.; Jacquenod, P.; Fuchsmann, C.; Philouze, P.
Abstract: Tracheoesophageal fistula results in persistent leakage of saliva into the trachea, prevents oral feeding, and predisposes to aspiration pneumonia. Large fistula closure may require a free flap to cover the defect. When the defect involves the tracheal area between the neck and the mediastinum, a tubeless field for optimal exposure can be advantageous. This article reports the use of veno-venous extracorporeal lung support, a known safe and efficient technique to support the patient's respiratory function, for this purpose. The typical veno-venous extracorporeal lung support setting includes a femoro-jugular bypass. The patient cases reported here had characteristics that precluded the use of the jugular vein, such as neck radiation dermatitis, previous radical neck dissection, and poor accessibility. Therefore a more rarely described femoro-femoral approach was used. The cases of three patients with persistent tracheoesophageal fistula who had free flap surgeries (two bi-paddled radial forearm free flap and one latissimus dorsi muscle free flap) assisted by femoro-femoral veno-venous extracorporeal lung support are reported.